Social Safety Nets and Gender : Learning from Impact Evaluations and World Bank Projects - Independent Evaluation Group (World Bank, Washington, DC, 2015)
Poverty reduction is the overarching objective of the World Bank Group and is reflected in the institution s commitment to the Millennium Development Goals (MDGs). More recently, the twin goals of the institution, eradicating extreme poverty by 2030 and boosting shared prosperity, expressed a renewed commitment toward the Bank Group s vision of a world free of poverty. This message is intimately related to another main goal of the institution: advancing gender equality. The shared prosperity goal calls for ensuring that men and women and boys and girls are included in the development process. This review focuses on a core set of poverty reduction interventions: Social Safety Net (SSN) programs. SSNs, a subset of social protection programs, are noncontributory transfer programs. Their main objective is to protect the poor against destitution and promoting equality of opportunity. The need to integrate gender considerations into the design of SSNs (and social protection interventions more generally) is an explicit objective of the World Bank Social Protection (SP) strategy. This report analyzes whether SSN interventions produce results and help to improve gender equality for men and women and boys and girls, either as a deliberate outcome or as an unplanned consequence. The report discusses whether SSN interventions aim to empower women and achieve greater gender equality, or impact other gender outcomes as one of their main goals. The report also looks at what type of actions and indicators these interventions adopt and what results they obtain. The report reviews evidence of results on SSN-specific outcomes.